ASSESSMENT OF GREY WATER DISPOSAL AND DIFFERENT TREATMENT OPTIONS FOR DOMIZ CAMP IN DUHOK CITY - MIZZOURI, NASHWAN MIZZOURI; ALGABBAN, MAHA MOHAMMED J.; HASSAN, HASSAN MOHAMMED (Journal of Duhok University, 2017)
The objectives of this study are to characterize the grey water from Domiz refugee camp, to evaluate the impacts of grey water on the properties of soil, and to suggest different treatment options. Grey water produced in this camp is about 1380 m3/d. The average grey water generation was estimated about 42 L/c.d. Grey water and soil samples were collected from stream channel at three different places. The results show concentrated grey water because of the water consumption was low inside the camp. Average Chemical Oxygen Demand (COD), Total Dissolved Solids (TDS), Total hardness, Calcium, Magnesium, Sodium, Potassium, Chloride, Sulfate, Nitrate, and phosphate values for the most polluted point were 1700, 1096, 540, 127, 65, 151, 29, 153, 232, 31 and 17 mg/L respectively. Impact of grey water on the properties of soil shows that Sodium Adsorption Ratio (SAR) values of soil samples increased compared to the control sample. Different treatment options were discussed for reusing the produced grey water. Because of the high level of TDS, availability of land, and low cost, construction wetland (CW) was selected as best option.